Terrorism and the Pandemic Weaponizing of COVID-19 - Gunaratna, Rohan (Berghahn Books, 2023)
The global pandemic has offered extraordinary opportunities for extremists and terrorists to mobilize themselves and revive as more powerful actors in the security landscape. But could these threat groups actually capitalize on the coronavirus crisis and advance their malevolent agendas? Utilizing the largest COVID-19-related terrorism database, the book presents an analysis built upon a quantitative and qualitative comparison between the nature of both the radical Islamist and the far-right-related threat in 2018 and 2020. It provides, for the first time, a true picture of novel trends since the pandemic outbreak.